The Zionist Bible : biblical precedent, colonialism and the erasure of memory - Masalha, Nur, 1957-; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Throughout the history of European imperialism the grand narratives of the Bible have been used to justify settler-colonialism. The Zionist Bible explores the ways in which modern political Zionism and Israeli militarism have used the Bible - notably the Book of Joshua and its description of the entry of the Israelites into the Promised Land - as an agent of oppression and to support settler-colonialism in Palestine. The rise of messianic Zionism in the late 1960s saw the beginnings of a Jewish theology of zealotocracy, based on the militant land traditions of the Bible and justifying the destruction of the previous inhabitants. The Zionist Bible examines how the birth and growth of the State of Israel has been shaped by this Zionist reading of the Bible, how it has refashioned Israeli-Jewish collective memory, erased and renamed Palestinian topography, and how critical responses to this reading have challenged both Jewish and Palestinian nationalism.
Framing the conflict: instrumentalizing the Hebrew Bible and settler-colonialism in Palestine -- Promised land and conquest narratives: Zionism and the 1948 Palestine Nakba -- Archaeology as civic religion: secular nationalist ideology, excavating the Bible and the de-Arabization of Palestine -- Colonialist imagination as a site of mimicry and erasure: the Israeli renaming project -- God's mapmakers: Jewish fundamentalism and the land traditions of the Hebrew Bible (1967 to Gaza 2013) -- Conclusion: the new scholarly revolution, and reclaiming the heritage of the disinherited and disenfranchised Palestinians.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Zionism and Judaism; Bible. -- Criticism, interpretation, etc; Electronic books